Arus Multikultural di Indonesia dalam Perspektif Pancasila, Islam, dan Kebangsaan: Multicultural Flow in Indonesia in the Perspective of Pancasila, Islam, and Nationality - Kharisma, Arrum; Zuhby, Nawal El; Purwanti, Juliastuti; Widyaningrum, Deta; Nur An-nisa, Aisyah; Rahman, Arif (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
Multiculturalism is an understanding of the diversity of culture and in this diversity is born a related understanding of equality, justice, peace, tolerance, and others. Multiculturalism in Pancasila uses the concept of gotong royong which allows all aspects of the Indonesian homeland to be recognized. In Islam, Allah SWT has explained, among others, in QS Al-Hujurat: 13 and QS Hud: 118-119 there is diversity between humans on earth. Multiculturalism in nationality according to historical records, the Indonesian nation has had diversity since the century before independence and has become a proud unity. This journal aims to analyze the currents of multiculturalism in Indonesia from the perspective of Pancasila, Islam, and nationality. This research method uses qualitative research methods using a library research approach. The main data sources in this research are multicultural currents in the perspective of Pancasila, Islamic nationality, and research articles that are relevant to this research. Collecting data in this study through a search of scientific literature related to the theme of this research. The results of this research conclude that multicultural implementation in the perspective of Pancasila, Islam, and nationality can be by building a harmonious relationship through multicultural teaching exercises, especially instructive exercises to grow insight and get attention, mentality, and behavior towards strict regional diversity, social and local. Religion and Pancasila have a strong relationship so that there is never a conflict between the two.